Public opinion analysis on social media about the establishment of Indonesia's New Capital City - Kadewandana, Donie; Cahyadiputra, Angga (Islamic Communication Journal, 2023)
One of the policies of President Joko Widodo's administration that is currently receiving various opinions is the issue of moving the Indonesian capital city from DKI Jakarta Province to East Kalimantan Province, to be precise, in Kutai Kartananegara Regency, which uses the name of the new capital city, Ibu Kota Nusantara (IKN). President Joko Widodo officially announced the transfer of the national capital on Monday, August 26, 2019, at the state palace. There were a variety of opinions regarding the capital city relocation policy. This study aims to find out the sentiment of public opinion regarding the move of the Indonesian capital to Kalimantan based on the hashtag #MovingCapitalCity on Twitter social media (now called "X"), as well as to understand the process of forming this public opinion. By using a quantitative approach based on content analysis with thematic analysis units in the form of pro, con, and neutral categorization, this study found that opinions on social media Twitter (now called "X") regarding the hashtag #MovingCapitalCity in the government's policy to move the country's capital tend to be contra or not supportive. Therefore, this study contributes to the power of community-based discourse, which is relevant to the principle of taghyir (change from bottom) in Islamic communication.***Salah satu kebijakan pemerintahan Presiden Joko Widodo yang kini menuai beragam opini adalah isu pemindahan ibu kota negara Indonesia dari Provinsi DKI Jakarta ke Provinsi Kalimantan Timur, tepatnya di Kabupaten Kutai Kartananegara yang menggunakan nama ibu kota baru, Ibu Kota Nusantara (IKN). Pemindahan ibu kota negara diumumkan secara resmi oleh Presiden Joko Widodo pada Senin, 26 Agustus 2019, di Istana Negara. Ada beragam pendapat mengenai kebijakan pemindahan ibu kota. Tujuan dari studi ini adalah untuk mengetahui sentimen opini masyarakat mengenai pemindahan ibu kota Indonesia ke Kalimantan berdasarkan hastag #MovingCapitalCity di media sosial Twitter (kini bernama “X”), serta memahami proses terbentuknya opini publik tersebut. Dengan menggunakan pendekatan kuantitatif berbasis analisis isi dengan unit analisis tematik berupa kategorisasi pro, kontra, dan netral, studi ini menemukan bahwa opini di media sosial Twitter (kini bernama “X”) mengenai tagar #MovingCapitalCity dalam kebijakan pemerintah untuk memindahkan ibu kota negara cenderung kontra atau tidak mendukung. Karena itu, studi ini berkontribusi bagi kuasa wacana berbasis masyarakat, yang relevan dengan prinsip taghyir (perubahan dari bawah) dalam komunikasi Islam.